2020
DOI: 10.1146/annurev-orgpsych-012119-045307
|View full text |Cite
|
Sign up to set email alerts
|

Asian Conceptualizations of Leadership: Progresses and Challenges

Abstract: By investigating broadly a contingency approach and implicit leadership theoretical perspectives with a multilevel lens as a starting point, this review highlights the potential for Asian conceptualizations of leadership. More specifically, by highlighting the important contingent role national culture plays in influencing leadership effectiveness, we review Asian conceptualizations of leadership that exist (e.g., paternalistic leadership style, paternalism, and guanxi in the leadership setting) in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 108 publications
0
30
0
Order By: Relevance
“…National culture defines employees’ values and expectations of leaders’ behaviors, thus making certain leadership behaviors more or less effective (e.g., Dickson et al, 2012; House et al, 2002; Oc, 2018). Power distance—“the extent to which a society accepts the fact that power in institutions and organizations is distributed unequally” (Hofstede, 1980, p. 45)—is particularly relevant to leadership effectiveness (Lee et al, 2020; Pratoom, 2018; Takeuchi et al, 2020). The cultural dimension represents whether employees view themselves as equal to others, influencing employees’ expectations of leadership behaviors (e.g., implicit prototypes; Offermann et al, 1994).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…National culture defines employees’ values and expectations of leaders’ behaviors, thus making certain leadership behaviors more or less effective (e.g., Dickson et al, 2012; House et al, 2002; Oc, 2018). Power distance—“the extent to which a society accepts the fact that power in institutions and organizations is distributed unequally” (Hofstede, 1980, p. 45)—is particularly relevant to leadership effectiveness (Lee et al, 2020; Pratoom, 2018; Takeuchi et al, 2020). The cultural dimension represents whether employees view themselves as equal to others, influencing employees’ expectations of leadership behaviors (e.g., implicit prototypes; Offermann et al, 1994).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In contrast, employees in higher power distance cultures respect formal authority, expect leaders to direct them and exercise power (House et al, 2002), view their leaders as parents or elders (Basabe & Ros, 2005), and are more likely to tolerate abusive treatment (Hon & Lu, 2016). Thus, leadership behaviors that align with egalitarian values are likely to be more effective in cultures with lower power distance, whereas leadership behaviors that align with authoritarian values are likely to be more effective in high power distance cultures (see Takeuchi et al, 2020).…”
Section: Contextual Moderatorsmentioning
confidence: 99%
“…Accordingly, they would have strong incentives to displace the responsibility of their behavioral choices to the leader. In contrast, when the authoritarian leader exhibits high benevolence and builds strong guanxi with employees, employees may feel strong obligations to the leader and thus are less likely to displace the responsibility of their behavior to the leader (Takeuchi et al, 2020). Instead, they would look for other ways to improve their performance (i.e., taking more initiatives in self-learning and making innovations at work).…”
Section: Discussionmentioning
confidence: 99%
“…As business environments become increasingly complex and uncertain, organizations continue to decentralize, gradually shifting the hierarchical focus of leadership towards a more collective and participative style (Yammarino, Salas, Serban, Shirreffs, & Shuffler, 2012). Despite this trend, researchers have found that authoritarian leadership, which emphasizes top-down communication and tight control (Farh & Cheng, 2000), remains common in China (Chen, Li, & Leung, 2017; Takeuchi, Wang, & Farh, 2020) and other cultures (De Hoogh & Den Hartog, 2009; Pellegrini & Scandura, 2008). Many researchers have paid considerable attention to understanding this phenomenon by examining the function of authoritarian leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Then, to address causality concerns in Study 1, we used an experimental design in Study 2 with a sample of working adults in which we tested Hypothesis 1 (leader humility affecting in-degree centrality in subordinates’ voice networks) and Hypothesis 2 (competitive work context as a moderator). Both studies were conducted in China where humility is a deep-rooted cultural virtue (Carus, 1909; Legge, 1991; Wilhelm & Baynes, 2011); while vertical collectivism and power distance are prevalent there, guanxi or a system of interpersonal relationships is essential (Takeuchi, Wang, & Farh, 2020). Similar humility research has been conducted in the Chinese context (Ou et al, 2014; Qin et al, 2020).…”
Section: Theory and Hypothesesmentioning
confidence: 99%